2017
DOI: 10.1021/acsami.7b16520
|View full text |Cite
|
Sign up to set email alerts
|

Effective Formaldehyde Capture by Green Cyclodextrin-Based Metal–Organic Framework

Abstract: A kind of metal-organic framework made from γ-cyclodextrin (γ-CD) and potassium ions were explored as excellent formaldehyde (HCHO) absorbents. The adsorption capacity and speed of γ-CD-MOF-K are both about 9 times higher than those of activated carbon, which are attributed to the porous structure and synergistic effect of hydrogen bonding and host-guest interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…It has been demonstrated that g-CD-K-MOF showed effective formaldehyde adsorption capability. 36 Fig. 5 showed the formaldehyde adsorption behaviour of g-CD-K-MOF and g-CD-K-MOF-H 2 S. In this study, formaldehyde gas was obtained by heating formaldehyde solution.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…It has been demonstrated that g-CD-K-MOF showed effective formaldehyde adsorption capability. 36 Fig. 5 showed the formaldehyde adsorption behaviour of g-CD-K-MOF and g-CD-K-MOF-H 2 S. In this study, formaldehyde gas was obtained by heating formaldehyde solution.…”
Section: Resultsmentioning
confidence: 90%
“…But it should be noticed that g-CD-K-MOF-H 2 S still showed a formaldehyde adsorption capacity three times higher than that of activated carbon. 36…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last two decades have witnessed a rapid development of research on metal–organic frameworks (MOFs), a notable class of highly crystalline polymeric materials, self‐assembled from organic linkers with metal ions or metal clusters . Owing to their diverse porous structures with various connectivity and symmetry, MOFs have been extensively explored for applications in numerous fields, ranging from adsorption to biomedical engineering .…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon is one of the most widely used materials for capture through adsorption . More recent studies utilize different nanoporous materials such as zeolites and metal‐organic framework . Not only adsorption but regenerating the adsorbents has been studied as well to see the desorption behaviour of VOCs…”
Section: Introductionmentioning
confidence: 99%